Sodium-ion battery positive electrode slurry and preparation method thereof
By adding slurry stabilizer to the positive electrode slurry of sodium ion battery and adopting dual planetary stirring, the problem of slurry flocculation of the positive electrode material of sodium ion battery during homogenization is solved, and the low viscosity and high flowability of the slurry are achieved , improves battery performance.
Patent Information
- Application Number
- CN202411636469.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
AI Technical Summary
The slurry flocculates during the homogenization process of sodium ion battery, resulting in an increase in viscosity, affecting the coating quality and reducing battery performance.
Add slurry stabilizers to the positive slurry of sodium ion battery, such as iron oxide, alumina, zirconia and titanium boride, combined with the dual planetary stirring method, control the vacuum degree and stirring temperature, and prepare good fluidity and low Viscosity slurry.
Significantly improve slurry flocculation, reduce viscosity, and improve coating quality, while not affecting the g capacity of sodium ion battery active materials, effectively solving the slurry flocculation problem.
Smart Images

Figure CN119481064A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries and relates to a sodium ion battery positive electrode slurry and a preparation method thereof. Background Art
[0002] Sodium-ion battery (NIB) is a secondary battery that uses sodium ions as charge carriers. Similar to lithium-ion batteries, sodium-ion batteries achieve the charging and discharging process by reversibly inserting and deinserting sodium ions between the positive electrode and the negative electrode. The advantages of sodium-ion batteries are that sodium resources are abundant, the cost is low, and they have similar working principles and structures to lithium-ion batteries. The positive electrode slurry of sodium-ion batteries is the key material for preparing the positive electrode of sodium-ion batteries, and is usually mixed with positive electrode active materials, conductive agents, binders and solvents. Among them, the positive electrode active material is the main component of the positive electrode of the sodium-ion battery, which is responsible for the insertion and deinsertion of sodium ions; the conductive agent is used to improve the conductivity of the positive electrode material and ensure the effective transmission of electrons; the binder is used to bond the positive electrode active material, the conductive agent and the conductive current collector (such as aluminum foil) together to maintain the structural integrity of the electrode; the solvent is used to dissolve the binder so that the slurry has good fluidity and coating properties.
[0003] However, excessive sodium salt is added to the positive electrode layered oxide material of sodium ion batteries during the production process, resulting in a large amount of sodium hydroxide, sodium carbonate and sodium bicarbonate remaining after the material is sintered, which is called residual alkali. Excessive residual alkali in the slurry process of the positive electrode material of sodium ion batteries will cause the slurry viscosity to increase or even flocculate, affecting the coating quality and thus causing the battery performance to decline. The usual solution is to add a weak acid, such as oxalic acid, to neutralize the residual alkali during the slurry preparation process. The addition of weak acid will chemically react with the positive electrode active material of the sodium ion battery, thereby affecting the gram capacity of the active substance.
[0004] Therefore, how to effectively solve the problem of slurry flocculation during the homogenization process of sodium-ion battery positive electrode materials without affecting the gram capacity of the active material has become an urgent problem to be solved in the development of sodium-ion batteries. Summary of the invention
[0005] The technical solution adopted by the present invention to solve the technical problem is: a sodium ion battery positive electrode slurry, including: a solid component and a liquid component solvent, the solid component includes: a positive electrode active material, a conductive agent, a binder, a dispersant, and a slurry stabilizer; the positive electrode material includes: a transition metal layered oxide material; the conductive agent includes: one or more combinations of conductive carbon black, Ketjen black, conductive graphite and carbon nanotubes; the dispersant includes: polyvinyl pyrrolidone; the slurry stabilizer includes: one or more combinations of iron oxide, aluminum oxide, zirconium oxide and titanium boride; the solvent includes: N-methylpyrrolidone;
[0006] Among the solid components, the mass ratio of positive electrode active material, conductive agent, binder, dispersant and slurry stabilizer is in the range of 92% to 95%: 3% to 5%: 2% to 3%: 1% to 3%: 1% to 2%; the mass ratio of liquid component to solid component is in the range of 4.2 to 5: 5 to 5.8;
[0007] The positive electrode slurry of the sodium ion battery is prepared by mixing a solid component and a liquid component solvent.
[0008] Preferably, the transition metal layered oxide materials include: NaFeO2, NaNiO2, NaMnO2, Na(Ni-Co-Mn)O2, Na(Ni-Fe-Mn)O2; NaFeO2 is characterized by low cost, abundant resources, but relatively poor electrochemical performance; NaNiO2 is characterized by high specific capacity, but poor thermal stability, and easy structural transformation; NaMnO2 is characterized by low cost, environmental friendliness, but low specific capacity; Na(Ni-Co-Mn)O2 is characterized by high specific capacity, good cycle performance and thermal stability; Na(Ni-Fe-Mn)O2 is characterized by high specific capacity, good cycle performance and thermal stability. Therefore, different transition metal layered oxide materials can be selected according to different needs.
[0009] The present invention also discloses a method for preparing a positive electrode slurry for a sodium ion battery. The method is used to prepare the positive electrode slurry for a sodium ion battery, and comprises the following steps:
[0010] Step 1: Mix and stir the binder and the solvent to obtain a glue solution;
[0011] Step 2: Add the conductive agent and the dispersant to the glue solution prepared in step 1, mix and stir to obtain a conductive glue solution;
[0012] Step 3: adding the positive electrode active material and the slurry stabilizer to the conductive glue prepared in step 2, mixing and stirring to obtain a positive electrode slurry;
[0013] Step 4: Defoam the positive electrode slurry prepared in step 3 to obtain a finished slurry.
[0014] Preferably, during the preparation process, the vacuum degree is maintained at ≤-95Kpa and the preparation temperature is maintained at 25°C to 28°C.
[0015] More preferably, in step 1, the stirring speed is 30-50 rpm, the rotation speed of the dispersion disk is 2200-3000 rpm, the corresponding linear speed is 5-8 m / s, and the stirring time is 60-90 min.
[0016] More preferably, in step 2, the stirring speed is 30 to 50 rpm, the dispersion disk rotation speed is 2200 to 3000 rpm, the corresponding linear speed is 5 to 8 m / s, and the stirring time is 120 to 180 min.
[0017] More preferably, in step 3, the stirring speed is 30 to 50 rpm, the dispersion disk rotation speed is 3000 to 4000 rpm, the corresponding linear speed is 7 to 11 m / s, and the stirring time is 120 to 180 min.
[0018] More preferably, in step 4, the revolution and reversal speed is 30 rpm, the dispersion disk rotation speed is 800 rpm, the corresponding linear speed is 1-3 m / s, and stirring is performed for 30 min.
[0019] More preferably, in the preparation process, a double planetary stirring method is used for stirring; the double planetary stirring method is to use two agitators (planetary agitators) in a stirring tank at the same time, and achieve efficient mixing and dispersion of materials through a special motion trajectory, thereby achieving efficient mixing, reducing dead angles, and improving product quality, and has the advantages of high efficiency, versatility, and strong adaptability.
[0020] The beneficial effects of the present invention are:
[0021] The present invention can significantly improve the effect of slurry flocculation and viscosity reduction by adding a slurry stabilizer to the positive electrode slurry of the sodium ion battery, while not affecting the gram capacity of the active material of the sodium ion battery. Therefore, the present invention can effectively solve the slurry flocculation problem of the positive electrode material of the sodium ion battery during the homogenization process. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The present invention is a schematic flow diagram of a sodium ion battery positive electrode slurry and a preparation method thereof. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the relevant technologies in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] refer to Figure 1In this embodiment, the mass fraction of the positive electrode active material in the total solid component is 92% to 95%; the mass fraction of the conductive agent in the total solid component is 3% to 5%; the mass fraction of the binder in the total solid component is 2% to 3%; the mass fraction of the dispersant in the total solid component is 1% to 3%; the mass fraction of the slurry stabilizer in the total solid component is 1% to 2%. The mass ratio of the solvent to the total solid component is (4.2 to 5): (5 to 5.8). In this embodiment, a double planetary stirring tank is used to prepare the slurry. The vacuum degree is controlled to be ≤95Kpa throughout the stirring process, and the tank temperature is 25 to 28°C.
[0025] Step 1: adding polyvinylidene fluoride to N-methylpyrrolidone, with an orbital speed of 30-50 rpm, a dispersion disk rotation speed of 2200-3000 rpm, a corresponding linear speed of 5.76-7.84 m / s, and a stirring time of 60-90 min to obtain a glue solution;
[0026] Step 2: Add one or more combinations of conductive carbon black, Ketjen black, conductive graphite and carbon nanotubes, and polyvinyl pyrrolidone to the glue solution, with an orbital speed of 30 to 50 rpm, a dispersion disk rotation speed of 2200 to 3000 rpm, a corresponding linear speed of 5.76 to 7.84 m / s, and a stirring time of 120 to 180 min to obtain a conductive slurry;
[0027] Step 3: Add the positive electrode active material and the slurry stabilizer to the conductive slurry, with a revolution speed of 30 to 50 rpm, a dispersion disk rotation speed of 3000 to 4000 rpm, a corresponding linear speed of 7.54 to 10.46 m / s, and a stirring time of 120 to 180 min to obtain a positive electrode active slurry;
[0028] Step 4: Defoam the slurry, with the revolution speed of 30 rpm, the rotation speed of the dispersion disk of 800 rpm, and the corresponding linear speed of 2.09 m / s. Stir for 30 minutes to obtain a finished slurry with good dispersion and good fluidity and a viscosity of 3000-6000 mPa·s.
[0029] Example
[0030] Step 1: Add 53.8 g of polyvinylidene fluoride into 1800 g of N-methylpyrrolidone, and stir at an orbital speed of 50 rpm and a rotational speed of 3000 rpm for 90 min to obtain a glue solution.
[0031] Step 2: Add 53.8 g of conductive carbon black, 537.6 g of CNTs slurry with a carbon nanotube content of 5% and 26.9 g of polyvinyl pyrrolidone into the glue solution, and stir for 120 min at an orbital speed of 50 rpm and a rotation speed of 3000 rpm to obtain a conductive glue solution.
[0032] Step 3: Add 2500 g of positive electrode layered oxide material and 26.9 g of titanium boride to the conductive glue, stir at an orbital speed of 50 rpm and a rotation speed of 4000 rpm for 120 min to obtain a positive electrode slurry.
[0033] Step 4: The revolution speed was adjusted to 30 rpm and set to reverse, the rotation speed was adjusted to 800 rpm, and stirred for 30 minutes to obtain a finished positive electrode slurry, and its viscosity was measured to be 3960 mPa·s.
[0034] In Example 2, Example 3 and Example 4, the titanium boride in step 3 of Example 1 is replaced with iron oxide, aluminum oxide and zirconium oxide respectively, the amount of each component added and the production process remain unchanged, and the mass proportion of layered oxide materials in the obtained positive electrode slurry is 93%. In Comparative Example 1, the titanium boride in step 3 of Example 1 is replaced with anhydrous oxalic acid, the amount of each component added and the production process remain unchanged, and the mass proportion of layered oxide materials in the obtained positive electrode slurry is 93%. In Comparative Example 2, the titanium boride in step 3 of Example 1 is removed, and only 2500g of positive electrode layered oxide material is added, the amount of other components added and the production process remain unchanged, and the mass proportion of layered oxide materials in the obtained positive electrode slurry is 93.94%. The proportion of solid components in the total mass of the finished slurries of the above embodiments and comparative examples is 53%.
[0035] The slurries of the embodiments and comparative examples were subjected to viscosity tests and button battery gram capacity tests, and the test methods were as follows: Slurry viscosity test: After discharging and sampling, a digital rotational viscometer was used, rotor No. 4 was selected, and the speed was set to 60 rpm. The test and data were recorded. Thereafter, the slurry was allowed to stand, and the viscosity was tested every half an hour using the same method. Three data were measured for each sample. Three parallel samples were taken for each embodiment or comparative example, and the average value was taken.
[0036] Button cell gram capacity test: After discharging and sampling, a manual scraper is used to scrape and coat the positive electrode sheet. The separator is a glass fiber paper separator, and the negative electrode is a metal sodium sheet. Three parallel samples are taken for each embodiment or comparative example, and the average value is taken. The following data are obtained from the two groups of experiments, as shown in Table 1:
[0037]
[0038] Table 1
[0039] The above data show that the four slurry stabilizers of the present invention all have different degrees of effect of improving slurry flocculation and reducing viscosity. Although the addition of oxalic acid in Comparative Example 1 also has a similar effect, it has a greater impact on the gram capacity of the material itself.
[0040] The viscosity of the discharge of the four embodiments and comparative example 1 is 4400±500mPa·s, and the viscosity of the slurry is lower than 9000mPa·s after standing for 1 hour, which is still within the coating window. The viscosity of the discharge of comparative example 2 exceeds 6000mPa·s. After standing for 30 minutes, the slurry flocculates and cannot be used for coating. This comparison shows that the slurry stabilizer and oxalic acid described in the present invention can reduce the viscosity of the layered oxide slurry of the sodium ion battery and improve the flocculation phenomenon. The test results of the gram capacity of the four embodiments and comparative example 2 are close, all of which are 160±2mAh / g for the first charge gram capacity, 155±2mAh / g for the first discharge gram capacity, and 96%±1 for the first efficiency. The first charge gram capacity, first discharge gram capacity and first efficiency of comparative example 1 are much lower than those of comparative example 2. This comparison shows that the slurry stabilizer described in the present invention has no effect on the electrochemical properties of the material.
[0041] In summary, the present invention can significantly improve the effect of reducing viscosity by flocculation of slurry by adding slurry stabilizer to the positive electrode slurry of sodium ion battery, and will not affect the gram capacity of active materials of sodium ion battery. The present invention can effectively solve the problem of slurry flocculation of positive electrode materials of sodium ion battery during homogenization. Therefore, the present invention has broad application prospects in the practical application of positive electrode slurry of sodium ion battery.
[0042] It should be emphasized that the above are only preferred embodiments of the present invention and do not impose any form of limitation on the present invention. Any simple modification of the above embodiments based on the technical essence of the present invention also falls within the protection scope of the present invention. Other equivalent changes and modifications still fall within the scope of the technical solution of the present invention.
Claims
1. A sodium ion battery positive electrode slurry, characterized in that: include: Solid components and liquid component solvents, the solid components comprising: positive electrode active material, conductive agent, binder, dispersant, slurry stabilizer; The positive electrode material includes: a transition metal layered oxide material; The conductive agent comprises: one or more combinations of conductive carbon black, Ketjen black, conductive graphite and carbon nanotubes; The dispersant includes: polyvinyl pyrrolidone; The slurry stabilizer includes: one or more combinations of iron oxide, aluminum oxide, zirconium oxide and titanium boride; The solvent includes: N-methylpyrrolidone; Among the solid components, the mass ratio of the positive electrode active material, the conductive agent, the binder, the dispersant, and the slurry stabilizer is in the range of 92% to 95%: 3% to 5%: 2% to 3%: 1% to 3%: 1% to 2%; The mass ratio of the liquid component to the solid component is in the range of 4.2-5:5-5.8; The sodium ion battery positive electrode slurry is prepared by mixing the solid component and the liquid component solvent.
2. A sodium ion battery positive electrode slurry according to claim 1, characterized in that: The transition metal layered oxide materials include: NaFeO2, NaNiO2, NaMnO2, Na(Ni-Co-Mn)O2, and Na(Ni-Fe-Mn)O2.
3. A method for preparing a positive electrode slurry for a sodium ion battery, characterized in that: The method is used to prepare the sodium ion battery positive electrode slurry according to any one of claims 1 to 2, and the method comprises the following steps: Step 1: Mix and stir the binder and the solvent to obtain a glue solution; Step 2: adding a conductive agent and a dispersant to the glue solution prepared in step 1, mixing and stirring to obtain a conductive glue solution; Step 3: adding the positive electrode active material and the slurry stabilizer to the conductive glue prepared in step 2, mixing and stirring to obtain a positive electrode slurry; Step 4: Defoam the positive electrode slurry prepared in step 3 to obtain a finished slurry.
4. The method for preparing a positive electrode slurry for a sodium ion battery according to claim 3, characterized in that: During the preparation process, the vacuum degree is maintained at ≤-95Kpa and the preparation temperature is maintained at 25°C to 28°C.
5. The method for preparing a positive electrode slurry for a sodium ion battery according to claim 4, characterized in that: In the step 1, the stirring speed is 30-50 rpm, the rotation speed of the dispersion disk is 2200-3000 rpm, the corresponding linear speed is 5-8 m / s, and the stirring time is 60-90 min.
6. The method for preparing a positive electrode slurry for a sodium ion battery according to claim 4, characterized in that: In the step 2, the stirring speed is 30 to 50 rpm, the rotation speed of the dispersion disk is 2200 to 3000 rpm, the corresponding linear speed is 5 to 8 m / s, and the stirring time is 120 to 180 min.
7. The method for preparing a positive electrode slurry for a sodium ion battery according to claim 4, characterized in that: In step 3, the stirring speed is 30 to 50 rpm, the rotation speed of the dispersion disk is 3000 to 4000 rpm, the corresponding linear speed is 7 to 11 m / s, and the stirring time is 120 to 180 min.
8. The method for preparing a positive electrode slurry for a sodium ion battery according to claim 4, characterized in that: In step 4, the revolution and reversal speed is 30 rpm, the dispersion disk rotation speed is 800 rpm, the corresponding linear speed is 1-3 m / s, and stirring is performed for 30 min.
9. The method for preparing a positive electrode slurry for a sodium ion battery according to claim 4, characterized in that: During the preparation process, a double planetary stirring method is used for stirring.
Citation Information
Cited By
Gel-free high-stability positive electrode slurry as well as preparation method and application thereof
CN120637488A
Gel-free high-stability positive electrode slurry, and preparation method and application thereof
CN120637488B
Dry-method material mixing process for lithium ion battery
CN120727724A
A dry mixing process for lithium ion batteries
CN120727724B